Viperatoxin-II: A novel viper venom protein as an effective bactericidal agent - Samy, R.; Stiles, B.; Chinnathambi, A.; Zayed, M.; Alharbi, S.; Franco, O.; Rowan, E.; Kumar, A.; Lim, L.; Sethi, Gautam (2015)
Infections caused by methicillin-resistant Staphylococcus aureus (MRSA) have become a rising threat to public health. There is an urgent need for development of promising new therapeutic agents against drug resistant bacteria like S. aureus. This report discusses purification and characterization of proteins from Indian Russell's viper snake venom. Novel 15-kDa proteins called "Viperatoxin" (VipTx-I and VipTx-II) were extracted from the whole venom and evaluated using in vitro antimicrobial experiments. The N-terminal amino acid sequence of "Viperatoxin" showed high sequence homology to daboiatoxin isolated from the same venom and also matched phospholipase A2 (PLA2) enzymes isolated from other snake venoms. In an in vitro plate assay, VipTx-II but not VipTx-I showed strong antimicrobial effects against S. aureus and Burkholderia pseudomallei (KHW & TES), Proteus vulgaris and P. mirabilis. The VipTx-II was further tested by a broth-dilution assay at 100-3.1µg/ml concentrations. The most potent bactericidal effect was found at the lowest dilutions (MICs of 6.25µg/ml) against B. pseudomallei, S. aureus and P. vulgaris (MICs of 12.25µg/ml). Electron microscopic investigation revealed that the protein-induced bactericidal potency was closely associated with pore formation and membrane damage, even at the lowest concentrations (<20µg/ml). The toxin caused a low level of cytotoxic effects as observed in human (THP-1) cells at higher concentrations. Molecular weight determinations of VipTx-II by sodium dodecyl sulfate-polyacrylamide gel electrophoresis showed one major, along with a few minor bands. The results indicate that VipTx-II plays a significant role in bactericidal and membrane damaging effects in vitro. Non-cytotoxic properties on human cells highlight it as a promising candidate for further evaluation of antimicrobial potential in vivo.